Exploring the Impact of Gender-Based Violence in South Africa - Corné Davis (The Thinker)
In 2021, Prof. Corné Davis, f rom the Department of Strategic Communication at the University of Johannesburg (UJ), approached KPMG South Africa regarding the publication of an updated research report on the cost of gender-based violence (GBV) to the South African economy, following a frequently quoted report titled ‘Too Costly to Ignore – The Economic Impact of Gender-Based Violence in South Africa’. A memorandum of agreement (MOA) was signed between UJ, Shared Value Africa Initiative, and KPMG South Africa to conduct research and to publish a new GBV report for South Africa. In the 2014 KPMG report, Prof. Koustuv Dalal of Mid Sweden University was cited with reference to the cost estimations he had done during a study in KwaZulu-Natal in 2011. Prof. Davis contacted Prof. Dalal by email to invite him to participate in the study.